1997
DOI: 10.1006/viro.1997.8611
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Six DNA Components of the Faba Bean Necrotic Yellows Virus Genome and Their Structural Affinity to Related Plant Virus Genomes

Abstract: Faba bean necrotic yellows virus (FBNYV) has a multicomponent circular ssDNA genome. In addition to a previously described genome component (C1) coding for a replicase-associated protein (Rep), five further components (C2 to C6) have now been identified. Each of the six components is about 1 kb in size, contains one major open reading frame (ORF) in the virion sense with a TATA box and polyadenylation signal, and has a noncoding region containing a highly conserved sequence possibly forming a stem-loop structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 0 publications
2
51
0
Order By: Relevance
“…The FBNYV genome has been reported to consist of at least six circular ssDNA components, each of which is about 1 kb (Katul et al, 1995(Katul et al, , 1997 and is probably encapsidated in a separate particle.…”
Section: Introductionmentioning
confidence: 99%
“…The FBNYV genome has been reported to consist of at least six circular ssDNA components, each of which is about 1 kb (Katul et al, 1995(Katul et al, , 1997 and is probably encapsidated in a separate particle.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental data and sequence evidence suggest that each DNA molecule, with a single exception, encodes only one protein (4,58). A set of five homologous genome components are common to both nano-and babuviruses: DNA-R encoding the master Rep (MRep) protein, which initiates rolling circle replication of all genomic DNAs of a nano-or babuvirus (25,53,55); DNA-S encoding the capsid protein (11,30,61); DNA-C encoding Clink, a cell-cycle link protein (3); DNA-M encoding a movement protein (60); and DNA-N encoding a nuclear-shuttle protein (60). Three other DNAs (DNAs-U1, -U2, and -U4) encoding proteins of as yet unknown functions have been identified from the nanoviruses FBNYV and MDV, and one further DNA (DNA-U3) was identified from the babuviruses BBTV (58) and ABTV (50).…”
mentioning
confidence: 99%
“…Molecular investigations on BBTV genome revealed that BBTV has isometric virions (Harding et al, 1991;Katul et al, 1997;Su et al, 2000), 18-20 nm in diameter, and a multicomponent genome consists of at least six circular single stranded DNA (ssDNA) component (BBTV DNA-1 to 6) ranging in size from 1108 bp to 1111 bp (Burns et al, 1994 andKaran et al, 1997;Wanitchakorn et al, 1997;Beetham et al, 1999). BBTV virions have a single coat protein of approximately 20 kDa (Thomas and Dietzen, 1991).…”
Section: Issn: 2319-7706 Volume 6 Number 6 (2017) Pp 398-411mentioning
confidence: 99%